Evidence-Based Management of Head and Neck Vascular Anomalies (Springer International Publishing, 2018)
This text addresses vascular anomalies and the management of these diverse and clinically challenging set of conditions which have significant impact on patient function, quality of life and, in certain cases, survival. The text covers each category and type of vascular anomaly and the unique diagnostic and therapeutic challenges they pose. The chapters will also include fundamental scientific literature pertaining to each specific condition to help clinicians and clinical researchers better assess and manage vascular anomalies of the head and neck. Each vascular condition will be supported with medical photographs and radiographic images, summaries of diagnostic and therapeutic options, a list of syndromes and genetic mutations known to be associated with each anomaly, case studies, and clinical and research pearls from national and international leaders in the field. Management of Head and Neck Vascular Anomalies: Evidenced-based Assessment will be an invaluable resource for otolaryngologists, plastic surgeons, general and general pediatric surgeons, orthopaedic surgeons, dermatologists, interventional radiologists, residents and fellows in these fields, and researchers with interest in vascular anomalies of the head and neck.